'Poppers Maculopathy' and the adverse ophthalmic outcomes from the recreational use of alkyl nitrate inhalants: a systematic review. (19th May 2023) - Bartolo, Caleb; Koklanis, Konstandina; Vukicevic, Meri
ABSTRACT: Objective: The aim of this systematic review and meta-analysis was to provide an overview of reported cases of poppers maculopathy and a statistical analysis of the clinical presentations, anatomical changes and treatment and follow-up of the rare disease. Methods: A systematic search of CINAHL, Embase and PubMed databases was conducted, including a search of the grey literature. Data were pooled to provide a summary of the clinical characteristics and outcomes of poppers maculopathy. Studies were critically appraised using the Joanna Briggs Institute or the Authority, Accuracy, Coverage, Objectivity, Date, Significance checklists. Results: Of the 493 articles obtained, 32 were included, consisting of 113 participants with a mean age of 40.2. Most patients were male with bilateral maculopathy and presented with either vision loss or a visual disturbance. Cessation of popper use was the most common form of management prescribed. The mean VA at baseline was 0.22 (logMAR units). For those followed-up, the mean VA significantly improved from 0.24 to 0.11 (Z = −5.800, p = <0.001). Bilateral yellow foveal spots were viewed on fundoscopy in 53 patients, and a sub-foveal disturbance of the ellipsoid layer was reported on spectral domain optical coherence tomography in 89 patients. By 6 months, SD-OCT anatomical changes mostly improved or resolved. Conclusion: Recreational users of poppers who develop maculopathy generally present with vision loss or a visual disturbance secondary to foveal disruption. Patients have a good visual prognosis, with cessation of poppers potentially having a role in improved outcomes. With the high prevalence of use among gay and bisexual men, awareness of related maculopathy and presenting symptoms by clinicians is important to mitigate side effects.